The Whistleblowing and Its Influence on Audit Planning, Procedures, and Quality - Zulia Hanum; Chiquita Elvina Trinanda (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Audit planning and audit procedures have a positive and significant impact on audit quality in public accounting firms in Medan, supported by effective violation reporting mechanisms. Specific Background: The implementation of accrual-based accounting in Indonesia based on Government Regulation No. 71 of 2010 aims to improve the quality of financial reporting, but compliance challenges remain persistent in the public sector. Knowledge Gap: Empirical studies on factors affecting audit quality in Indonesia are still limited, especially comprehensive quantitative research using advanced statistical methods. Objective: To analyse the influence of audit planning and audit procedures on audit quality and the moderating role of violation reporting. Method: This study uses an associative quantitative approach with questionnaire data from auditors, analysed through SEM-PLS. Results: Audit planning and audit procedures significantly influence audit quality, while violation reporting strengthens this relationship. Novelty: This study integrates violation reporting as a moderating variable in analysing the impact of audit planning and audit procedures on audit quality using SEM-PLS. Implications: Strengthening audit planning, ensuring compliance with audit procedures, and implementing an effective violation reporting system are essential for improving audit quality, transparency, and reliability.